Quality Assessment of the Center to Advance Palliative Care in the ICU Screening Tool- Thai Version: A Retrospective Study - Prabkaew, Souwaluk; Kanokwan Nokkasam; Paredah Billateh; Petpichetchian, Wongchan (Thai Journal of Nursing and Midwifery Practice, 2023)
This retrospective study aimed to assess the quality of the Center to Advance Palliative Care in the ICU Screening Tool-Thai Version (CAPC-ICU Thai) concerning its sensitivity, specificity and predictive validity. The medical records of 207 adult patients admitted to the intensive care unit of a private hospital between January 2018 and June 2019 were randomly retrieved. The CAPC-ICU was back-translated into Thai with permission granted from the developers. Inter-rater reliability was conducted between two raters yielding a Kappa coefficient of 1.00. Demographic data and the death rate were analyzed using descriptive statistics. Sensitivity and specificity analysis was performed to determine the best cut-off score indicating the probability of palliative care needs six months before death by using Receiver Operating Characteristics (ROC) curve analysis. Logistic regression analysis was conducted to determine the predictive validity of the CAPC-ICU Thai. The findings showed that 11.1% of patients died within six months. The CAPC-ICU Thai scores ranged from 0-10. The cut-off score of 4 provided the best determination of the need for palliative care with a sensitivity of 0.826 and a specificity of 0.908. The area under the ROC curve to predict the outcome was 92.8%. For predictive validity, logistic regression analysis controlling for age and gender revealed that the odds of death outcome significantly increased by 2.1. Implementing the CAPC-ICU Thai as a screening tool for patients admitted to ICUs is recommended so that palliative care can be planned for patients and family members.